Engaging sense of place in an environment of change: youth, identity and place-based learning activities in environmental education - Farrington, Katie (Rhodes University, Faculty of Education, Department of Education, 2006)
This case study investigates sense of place of youth amidst a background of change in postapartheid South Africa. As used in this study, sense of place refers to the attachments made to both physical and social places, and the social and cultural interactions and meanings associated with such places. The research was conducted with a group of 13 young adults at Mary Waters Senior Secondary School in Grahamstown. The literature suggests that the changes that occur in the lives of the participants at school-leaving age such as new opportunities to identify with global aspirations, tend to influence their sense of place in local contexts. Social change that occurs due to globalising forces such as access to new technologies and improved personal mobility, also influences sense of place in this context. Another integral factor is the structural influence of changing cultural and educational norms. These notions form part of the backdrop of this study. The research project was developed in response to calls for learning approaches that are situated more in local contexts and which include the youth as intrinsic participants informing environmental education approaches. This research draws attention to the significance of finding sustainable ways that enhance opportunities for agency on the part of the youth in future local and global environmental care-taking. The study took place over a period of 15 months in which time the participants undertook place-based activities in their communities around self-identified environmental concerns. The study was intentionally generative in approach as this allowed the voices of the participants and their environmental perspectives to be considered in developing methods and activities that were suitable to their particular contexts and interests. The study highlights the relevance of particular social contexts, through the perspectives of people and in this case learners, as key to environmental education enquiries. The combination of approaches that consider: a) knowledge about social context, b) the educational intervention (place-based activities) and, c) the situated social capital of the participants, all form the basis of meaningful pedagogical engagements and serve to address my research question: How is learners' sense of place developed and articulated through place-based activities, and what are the implications for environmental education amidst a contemporary landscape of change in South Africa?
Keywords: Environmental education -- South Africa -- Grahamstown; Place-based education -- South Africa -- Grahamstown; Educational change -- South Africa Youth -- South Africa -- Social conditions